Minority stress, distress, and suicide attempts in three cohorts of sexual minority adults: A U.S. probability sample - Meyer, Ilan H.; Russell, Stephen T.; Hammack, Phillip L.; Frost, David M.; Wilson, Bianca D. M. (PloS one, 2021)
During the past 50 years, there have been marked improvement in the social and legal environment of sexual minorities in the United States. Minority stress theory predicts that health of sexual minorities is predicated on the social environment. As the social environment improves, exposure to stress would decline and health outcomes would improve. We assessed how stress, identity, connectedness with the LGBT community, and psychological distress and suicide behavior varied across three distinct cohorts of sexual minority people in the United States. Using a national probability sample recruited in 2016 and 2017, we assessed three a priori defined cohorts of sexual minorities we labeled the pride (born 1956–1963), visibility (born 1974–1981), and equality (born 1990–1997) cohorts. We found significant and impressive cohort differences in coming out milestones, with members of the younger cohort coming out much earlier than members of the two older cohorts. But we found no signs that the improved social environment attenuated their exposure to minority stressors—both distal stressors, such as violence and discrimination, and proximal stressors, such as internalized homophobia and expectations of rejection. Psychological distress and suicide behavior also were not improved, and indeed were worse for the younger than the older cohorts. These findings suggest that changes in the social environment had limited impact on stress processes and mental health for sexual minority people. They speak to the endurance of cultural ideologies such as homophobia and heterosexism and accompanying rejection of and violence toward sexual minorities.